Synthesis of gradient copolysiloxanes by simultaneous copolymerization of cyclotrisiloxanes and mechanism for kinetics inverse between anionic and cationic ring‐opening polymerization. Issue 6 (13th October 2015) - Fei, Hua‐Feng; Han, Xiaojie; Liu, Bozheng; Gao, Xiyin; Wang, Qian; Zhang, Zhijie; Xie, Zemin
ABSTRACT: Trifluoropropylmethylsiloxane–phenylmethylsiloxane gradient copolysiloxanes were synthesized by anionic and cationic ring‐opening polymerization (ROP) of 1, 3, 5‐tris(trifluoropropylmethyl)cyclotrisiloxane ( D 3 F ) and phenylmethylcyclotrisiloxane ( D 3 Ph ). The analysis of reactivity ratios revealed that the reactivity of D 3 F toward anionic ROP was higher than that of D 3 Ph ; however, D 3 F exhibited lower reactivity compared with D 3 Ph during the cationic ROP. AB and BAB type gradient copolymers were obtained because of a difference in the reactivity of the monomers. The microstructure of copolymers was characterized by 29 Si NMR spectroscopy, gel permeation chromatography, and differential scanning calorimetry. Furthermore, the mechanism for kinetics inverse of copolymerization was proposed based on the results of the optimized molecular configuration. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 835–843 Abstract : The reactivity of D 3 F toward anionic ROP was higher than that of D 3 Ph ; however, D 3 F exhibited lower reactivity compared with D 3 Ph during the cationic ROP. Thus, AB and BAB type gradient copolymers were obtained because of a difference in the reactivity of the monomers.